Sequence-dependent termination of in vitro DNA synthesis by cis- and trans-diamminedichloroplatinum (II). - Pinto, A L (1985)
Inhibition of DNA replication by the antitumor drug cis-diamminedichloroplatinum (II) (cis-DDP) has been proposed to be responsible for its cytotoxicity. Treatment of primed phage M13 mp8 viral DNA templates with the drug followed by second-strand synthesis using large fragment DNA polymerase I reveals that cis-DDP forms an adduct with DNA that inhibits DNA synthesis in vitro. This inhibition occurs at all (dG)n (n greater than or equal to 2) sequences in the template strand, confirming that these regions are the major cis-DDP binding sites on DNA. trans-Diamminedichloroplatinum (II), which is inactive as a drug, also forms adducts that inhibit DNA synthesis. Although considerably lower specificity is observed with the trans isomer, there appears to be a preference for d(GpNpG) sequences, where N is any intervening nucleotide. The monofunctional adduct formed between chlorodiethylenetriamineplatinum(II) chloride and DNA does not inhibit DNA synthesis in this system.